MENSAGEM DOS DIRIGENTES - Friede, Reis; Azulay Neto, Messod; Oliveira Júnior, Osair Victor de (Revista da Seção Judiciária do Rio de Janeiro - Auditorium; v. 24 n. 49 (2020): II Seminário de Direitos Humanos: em tempos de PandemiaDO - 10.30749/2177-8337.v24n49p11-12, 2020)
MENSAGEM DOS DIRIGENTES